2015
DOI: 10.1007/s11920-015-0579-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sexual Images in Online and Offline Sexual Behaviour With Minors

Abstract: Sexual images have long been associated with sexual interest and behaviour with minors. The Internet has impacted access to existing content and the ability to create content which can be uploaded and distributed. These images can be used forensically to determine the legality of the behaviour, but importantly for psychiatry, they offer insight into motivation, sexual interest and deviance, the relationship between image content and offline sexual behaviour, and how they might be used in online solicitation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Where chat logs have been used, these involved adults pretending to be children. In addition, while the use of sexual images has been noted in both offender and victim studies, this has not been critically examined (Quayle and Newman 2015). The aims of the present study were to use online reports from the public to Cybertip.ca to explore: the types of behaviour that alerted concerned adults, and occasionally young people, to make a report; information available about the young person; information about the suspect, and how both suspect and young people interacted in the exchange of text and images.…”
Section: Introductionmentioning
confidence: 99%
“…Where chat logs have been used, these involved adults pretending to be children. In addition, while the use of sexual images has been noted in both offender and victim studies, this has not been critically examined (Quayle and Newman 2015). The aims of the present study were to use online reports from the public to Cybertip.ca to explore: the types of behaviour that alerted concerned adults, and occasionally young people, to make a report; information available about the young person; information about the suspect, and how both suspect and young people interacted in the exchange of text and images.…”
Section: Introductionmentioning
confidence: 99%
“…There is a trend that internet users tend to be younger in China [ 38 ]. Quayle and Newman [ 39 ] indicated that some images and messages with sexual inducement on the internet offered sexual motivation and interest to users, especially for minors. Therefore, it is necessary to pay attention to the internet-based HIV prevention and testing services for minors.…”
Section: Discussionmentioning
confidence: 99%
“…adicción a Internet) hasta nuevas formas de delinquir (ej. abuso sexual online), tal como lo han documentado diversos autores (Berner y Santander, 2012;Block, 2008;Quayle y Newman, 2015).…”
Section: Introductionunclassified